Midazolam and ketamine induction before halothane anaesthesia in ponies: cardiorespiratory, endocrine and metabolic changes - Luna, SPL; Taylor, P. M.; Massone, F. (Blackwell Science, 1997)
Six Welsh gelding ponies were premedicated with 0.03 mg/kg of acepromazine intravenously (i.v.) prior to induction of anaesthesia with midazolam at 0.2 mg/kg and ketamine at 2 mg/kg i.v.. Anaesthesia was maintained for 2 h using 1.2% halothane concentration in oxygen. Heart rate, electrocardiograph (EGG), arterial blood pressure, respiratory rate, blood gases, temperature, haematocrit, plasma arginine vasopressin (AVP), dynorphin, beta-endorphin, adrenocorticotropic hormone (ACTH), cortisol, dopamine, noradrenaline, adrenaline, glucose and lactate concentrations were measured before and after premedication, immediately after induction, every 20 min during anaesthesia, and at 20 and 120 min after disconnection. Induction was rapid, excitement-free and good muscle relaxation was observed. There were no changes in heart and respiratory rates, Decrease in temperature, hyperoxia and respiratory acidosis developed during anaesthesia and slight hypotension was observed (minimum value 76 +/- 10 mm Hg at 40 mins), No changes were observed in dynorphin, beta-endorphin, ACTH, catecholamines and glucose, Plasma cortisol concentration increased from 220 +/- 17 basal to 354 +/- 22 nmol/L at 120 min during anaesthesia; plasma AVP concentration increased from 3 +/- 1 basal to 346 +/- 64 pmol/L at 100 min during anaesthesia and plasma lactate concentration increased from 1.22 +/- 0.08 basal to 1.76 +/- 0.13 mmol/L at 80 min during anaesthesia, Recovery was rapid and uneventful with ponies taking 46 +/- 6 min to stand. When midazolam/ketamine was compared with thiopentone or detomidine/ketamine for induction before halothane anaesthesia using an otherwise similar protocol in the same ponies, it caused slightly more respiratory depression, but less hypotension. Additionally, midazolam reduced the hormonal stress response commonly observed during halothane anaesthesia and appears to have a good potential for use in horses.